Water-based multifunctional binder capable of recycling positive electrode material and preparation method and application of water-based multifunctional binder

By developing a water-based multifunctional binder, the problems of complex lithium-ion battery recycling technology and low material utilization efficiency are solved, and the efficient recycling of cathode materials and the protection and recovery of electrochemical properties are achieved.

CN119912885AInactive Publication Date: 2025-05-02QINGDAO YINGKE PRECISION RUBBER & PLASTIC CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510059278.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium-ion battery recycling technology is complex and cumbersome, and a single recycling method is difficult to meet the efficient use of materials. It usually requires the coordinated effect of multiple methods.

Method used

An aqueous multifunctional binder was developed to prepare a binder that can form a stable CEI layer during the circulation, protect the positive electrode material and achieve its recovery by mixing chitosan, acrylic organic acids and N-hydroxysuccinimide with water, and cross-linking and freeze-drying.

Benefits of technology

This binder significantly improves the electrochemical properties of the olivine-type cathode material, protects the cathode material from corrosion by electrolyte, and uses alkaline solution recovery and lithium replenishment methods to make the recovered cathode material still have excellent electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005242369110000011
    Figure HDA0005242369110000011
  • Figure HDA0005242369110000012
    Figure HDA0005242369110000012
  • Figure HDA0005242369110000021
    Figure HDA0005242369110000021
Patent Text Reader

Abstract

The invention provides a water-based multifunctional binder capable of recycling a positive electrode material and a preparation method and application of the water-based multifunctional binder, and belongs to the technical field of lithium ion battery binders, the preparation method comprises the following steps: 1) mixing chitosan, acrylic acid organic acid and N-hydroxysuccinimide with water, and stirring to obtain a uniform mixed solution; 2) placing the mixed solution obtained in the step 1) under an ultraviolet lamp for irradiation crosslinking to obtain a colloidal liquid; and 3) freeze-drying the colloidal liquid obtained in the step 2) to obtain the binder. The adhesive prepared by the invention forms a stable CEI layer in the circulation process, so that the Li < + > transmission resistance is reduced, and the electrochemical performance of the olivine type positive electrode material is obviously improved. Meanwhile, the recycled positive pole piece is immersed in an alkaline solution, the positive pole material can be recycled, and sintering is carried out through a lithium supplementing method, so that the recycled positive pole material still has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery binders, and in particular relates to an aqueous multifunctional binder capable of realizing the recovery of positive electrode materials, and a preparation method and application thereof. Background Art

[0002] In order to combat climate change, many large economies are trying to develop strategies to reduce CO2 emissions, and to achieve these goals, electric vehicles (EVs) are seen as a key energy-saving technology as they produce significantly lower emissions over their entire life cycle compared to equivalent gasoline and diesel vehicles. However, in order to achieve sustainability, efficient recycling of batteries is essential to help secure key strategic resources such as lithium, manganese, cobalt and nickel.

[0003] Currently, there are two main routes for recycling these batteries. Pyrometallurgy uses high temperatures to melt the batteries to form alloys, which are then processed to recover valuable metals such as Li, Co, Cu and Ni. An advantage of this technology is that the batteries do not have to be sorted before the smelting process. However, the process has some disadvantages, such as the loss of volatile and critical materials (such as lithium, graphite and phosphorus) and toxic emissions. In addition, the high-temperature processing is an energy-intensive industry and only allows a limited amount of processing capacity (i.e., only a relatively small amount of battery waste can be processed in a given time). Hydrometallurgy can be used to recycle batteries without prior pyrometallurgical processing, in which the batteries (obtained by disassembling battery packs) are first shredded. Subsequently, the battery casings, separators and separators are removed to form a fraction commonly referred to as the "black mass", which is the smallest fraction after screening and contains a mixture of negative and positive electrode materials. The black mass is then chemically treated. By far the most common reagent combination in the literature is sulfuric acid (H 2 SO 4 ) as leaching acid and reducing acid, which has been shown to improve leaching efficiency.

[0004] In the above technical solutions, the recycling process is complicated and the operation is cumbersome. Single recycling cannot meet the efficient utilization of materials, and usually two or three methods are needed to coordinate. Summary of the invention

[0005] In view of this, the object of the present invention is to provide an aqueous multifunctional binder that can realize the recycling of positive electrode materials, and a preparation method and application thereof. The binder prepared by the present invention forms a stable CEI layer during the cycle process, which significantly improves the electrochemical properties of the olivine-type positive electrode material, and at the same time plays a role in protecting the positive electrode material to avoid corrosion of the electrolyte during cyclic overcharge and material failure. In addition, the positive electrode sheet after the cycle can be immersed in an alkaline solution to recover the positive electrode material, and sintered by a lithium replenishment method, so that the recovered positive electrode material still has excellent electrochemical properties. The positive electrode sheet assembled with the binder provided by the present invention can be "directly recycled" to obtain positive electrode material powder, and the electrochemical properties can be restored in combination with a lithium replenishment strategy. Direct recycling aims to revitalize the positive electrode material with minimal changes, while removing the binder and redistributing the positive electrode material.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing an aqueous multifunctional binder capable of recycling positive electrode materials, comprising the following steps:

[0008] 1) mixing chitosan, acrylic acid, N-hydroxysuccinimide and water, and stirring to obtain a uniform mixed solution;

[0009] 2) placing the mixed solution obtained in step 1) under ultraviolet light for cross-linking to obtain a colloidal liquid;

[0010] 3) freeze-drying the colloidal liquid obtained in step 2) to obtain a binder.

[0011] Preferably, the acrylic organic acid includes at least one of acrylic acid, polyacrylic acid, and 2-(trifluoromethyl)acrylic acid.

[0012] Preferably, the mass ratio of the acrylic acid, chitosan and N-hydroxysuccinimide is 55-65:3-5:0.5-1.5.

[0013] Preferably, the power of the ultraviolet lamp is 16-18W, and the irradiation time is 0.5-1h.

[0014] Preferably, the freeze-drying time is 12 to 24 hours.

[0015] The present invention also provides an aqueous multifunctional binder prepared by the above preparation method and capable of realizing the recovery of positive electrode materials.

[0016] The present invention also provides an application of an aqueous multifunctional binder capable of realizing the recovery of positive electrode materials in protecting the positive electrode materials from corrosion by electrolytes during electrochemical cycles.

[0017] The present invention also provides an application of an aqueous multifunctional binder capable of recycling positive electrode materials in recycling positive electrode materials.

[0018] Preferably, the solution used to recover the positive electrode material is an alkaline solution, and the pH value of the alkaline solution is 11-13.

[0019] Preferably, the method of recovering the positive electrode material further comprises replenishing lithium on the recovered positive electrode material to obtain a lithium-replenished positive electrode material.

[0020] The present invention has the following beneficial effects:

[0021] 1. The present invention uses acrylic acid composite chitosan as a raw material and N-hydroxysuccinimide as an initiator, so that the bonding performance is greatly improved and the cracking phenomenon of the electrode during the cycle process is effectively suppressed.

[0022] 2. The experimental method of the present invention is simple, easy to operate, and the solvent is deionized water, which is more environmentally friendly and green compared to the traditional preparation method.

[0023] 3. The binder of the present invention forms a stable CEI layer during the cycle of the positive electrode material to protect the positive electrode material from corrosion. At the same time, the stable CEI layer has excellent proton conductivity and excellent electrochemical performance under 1C cycle.

[0024] 4. The present invention is a recyclable binder with a simple and efficient recycling process, which complies with the concept of green environmental protection. The binder still has excellent electrochemical properties after recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the lithium iron phosphate positive electrode sheet prepared by the binder in Example 2 before cycling;

[0026] Figure 2 This is a SEM image of the lithium iron phosphate positive electrode sheet prepared by the binder in Example 2 after 50 cycles;

[0027] Figure 3 A comparison chart of the cycle performance of lithium iron phosphate batteries prepared with the binders in Example 1, Example 2 and Comparative Example 1 at a current density of 1C;

[0028] Figure 4 is the XRD pattern of lithium iron phosphate after recovery in Example 6;

[0029] Figure 5 This is the electrochemical performance diagram of lithium iron phosphate after recovery in Example 6. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing an aqueous multifunctional binder capable of recycling positive electrode materials, comprising the following steps:

[0031] 1) mixing chitosan, acrylic acid, N-hydroxysuccinimide and water, and stirring to obtain a uniform mixed solution;

[0032] 2) placing the mixed solution obtained in step 1) under ultraviolet light for cross-linking to obtain a colloidal liquid;

[0033] 3) freeze-drying the colloidal liquid obtained in step 2) to obtain a binder.

[0034] The present invention has no special limitation on the sources of the chitosan, acrylic acid organic acid and N-hydroxysuccinimide, and conventional commercial products in the art may be used.

[0035] In the present invention, the water is preferably deionized water.

[0036] The present invention has no particular limitation on the stirring method, but preferably a stirrer is used for stirring.

[0037] In the present invention, the acrylic organic acid preferably includes at least one of acrylic acid, polyacrylic acid, and 2-(trifluoromethyl)acrylic acid.

[0038] In the present invention, the mass ratio of the acrylic acid, chitosan and N-hydroxysuccinimide is preferably 55-65:3-5:0.5-1.5.

[0039] In the present invention, acrylic acid accounts for 20-30 wt%, chitosan accounts for 1-2 wt%, and N-hydroxysuccinimide accounts for 0.5 wt%.

[0040] In the present invention, the power of the ultraviolet lamp is preferably 16 to 18 W, and the irradiation time is preferably 0.5 to 1 h.

[0041] The present invention also provides an aqueous multifunctional binder prepared by the above preparation method and capable of realizing the recovery of positive electrode materials.

[0042] In the present invention, the solution used to recover the positive electrode material is preferably an alkaline solution, the solute of the alkaline solution is LiOH or NaOH, and the pH value of the alkaline solution is preferably 11-13.

[0043] In the present invention, the recovery of the positive electrode material further includes replenishing lithium on the recovered positive electrode material to obtain a lithium-replenished positive electrode material.

[0044] In the present invention, the lithium supplement preparation method is preferably to place the recovered positive electrode material powder in a LiOH solution and perform hydrothermal treatment.

[0045] In the present invention, in the lithium supplement preparation method, the pH value of the LiOH solution is preferably controlled to be 11-13, the hydrothermal temperature is preferably 150-200° C., and the time is preferably 10-12 h.

[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0047] Example 1

[0048] 3g acrylic acid, 50mg N-hydroxysuccinimide and 200mg chitosan were dissolved in 10ml deionized water, stirred evenly and then moved to a UV lamp for 18W irradiation for 1h to obtain a colloidal liquid, which was moved to a freeze dryer and freeze-dried for 12h to obtain the binder, which was recorded as PCN binder. The lithium iron phosphate positive electrode material, conductive additive and binder were stirred in a mass ratio of 8:1:1, and the obtained slurry was evenly coated on aluminum foil and dried in a vacuum drying oven, and the pole piece was subjected to performance testing.

[0049] Example 2

[0050] 3g 2-(trifluoromethyl)acrylic acid, 50mg N-hydroxysuccinimide and 200mg chitosan were dissolved in 10ml deionized water, stirred evenly and then moved to a UV lamp for 18W irradiation for 1h to obtain a colloidal liquid, which was moved to a freeze dryer and freeze-dried for 12h to obtain the binder, which was recorded as PCN-F binder. The lithium iron phosphate positive electrode material, conductive additive and binder were stirred in a mass ratio of 8:1:1, and the obtained slurry was evenly coated on aluminum foil and dried in a vacuum drying oven, and the pole piece was subjected to performance testing.

[0051] Example 3

[0052] 3g polyacrylic acid, 50mg N-hydroxysuccinimide and 200mg chitosan were dissolved in 10ml deionized water, stirred evenly and then moved to a UV lamp for 18W irradiation for 1h to obtain a colloidal liquid, which was moved to a freeze dryer and freeze-dried for 12h to obtain the binder, which was recorded as PCN-A binder. The lithium iron phosphate positive electrode material, conductive additive and binder were stirred in a mass ratio of 8:1:1, and the obtained slurry was evenly coated on aluminum foil and dried in a vacuum drying oven, and the pole piece was subjected to performance testing.

[0053] Example 4

[0054] The positive electrode sheet using PCN binder is assembled into a battery for electrochemical cycling. After the cycle is completed, the battery is dismantled to obtain the positive electrode sheet after the cycle. The positive electrode sheet is immersed in a 1 mol / L NaOH solution, the positive electrode powder is peeled off from the current collector, and the binder is hydrolyzed, and the positive electrode powder is collected.

[0055] Example 5

[0056] Different from Example 4, the binder used this time is PCN-F binder. The positive electrode sheet using PCN-F binder is assembled into a battery for electrochemical cycling. After the cycle is completed, the battery is disassembled to obtain the positive electrode sheet after the cycle. The positive electrode sheet is immersed in 1 mol / L NaOH solution, the positive electrode powder is peeled off from the current collector, and the binder is hydrolyzed, and the positive electrode powder is collected.

[0057] Example 6

[0058] The positive electrode powder obtained in Example 5 was supplemented with lithium. Specifically, after collecting the positive electrode powder, it was placed in a 100 ml reactor, and 70 ml of a 1 mol / L LiOH solution was added, and hydrothermal treatment was performed at 200°C for 10 hours. The positive electrode powder after supplementation with lithium, the conductive additive, and the PCN-F binder were stirred in a mass ratio of 8:1:1, and the obtained slurry was evenly coated on an aluminum foil, dried in a vacuum drying oven, and the electrode was subjected to a performance test.

[0059] Comparative Example 1

[0060] This comparative example uses traditional commercial binder PVDF, and the lithium iron phosphate positive electrode material, conductive additive, and binder are stirred in a mass ratio of 8:1:1. The resulting slurry is evenly coated on aluminum foil and dried in a vacuum drying oven, and the electrode is subjected to performance testing.

[0061] Comparative Example 2

[0062] In this comparative example, commercial polyacrylic acid was used to stir the lithium iron phosphate positive electrode material, the conductive additive, and the binder in a mass ratio of 8:1:1. The resulting slurry was evenly coated on an aluminum foil and dried in a vacuum drying oven. The electrode was subjected to a performance test.

[0063] Example 7

[0064] Figure 1 This is a SEM image of the lithium iron phosphate positive electrode sheet prepared by the binder in Example 2 before cycling. No obvious cracks were found after drying, which shows that the prepared binder has excellent bonding properties and ensures a solid network between the positive electrode material, the conductive additive and the current collector.

[0065] Figure 2 This is a SEM image of the lithium iron phosphate positive electrode sheet prepared by the binder in Example 2 after 50 cycles. After the positive electrode material was cycled for 50 cycles, SEM testing revealed that there was a protective film on its surface, which effectively protected the positive electrode material from corrosion, and the uniform CEI layer gave it excellent electrochemical performance.

[0066] Figure 3The figure is a comparison of the cycling performance of lithium iron phosphate batteries prepared with the binders in Examples 1 and 2 and Comparative Example 1 at a current density of 1C. The performance of the conventional PVDF binder will gradually decay during the cycling process, which is mainly due to the insufficient adhesion of PVDF. However, the PCN binder and PCN-F binder are stable in cycling, and the first cycle discharge capacity at 1C can reach 160mAh g -1 , the capacity retention rate after 500 cycles is 98.2%.

[0067] Figure 4 This is the XRD diagram of the lithium iron phosphate after recovery in Example 6. After comparison with the standard card (PDF#440-1499), it is found that its crystal structure still belongs to the olivine type positive electrode structure, indicating that the recovered powder is a lithium iron phosphate positive electrode material.

[0068] Figure 5 The figure is the electrochemical performance diagram of the recycled lithium iron phosphate in Example 6. The recycled powder was assembled into a battery and its cycle performance at 1C was tested. The experimental results showed that the initial capacity of the recycled positive electrode material at 1C was 155.2 mAh g -1 After 300 cycles, there is still 139.1 mAh g -1 The high capacity further illustrates the successful material recovery.

[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an aqueous multifunctional binder capable of recycling positive electrode materials, characterized in that: The following steps are involved: 1) mixing chitosan, acrylic acid, N-hydroxysuccinimide and water, and stirring to obtain a uniform mixed solution; 2) placing the mixed solution obtained in step 1) under ultraviolet light for cross-linking to obtain a colloidal liquid; 3) freeze-drying the colloidal liquid obtained in step 2) to obtain a binder.

2. The method for preparing an aqueous multifunctional binder capable of recycling positive electrode materials according to claim 1, characterized in that: The acrylic organic acid in step 1) includes at least one of acrylic acid, polyacrylic acid, and 2-(trifluoromethyl)acrylic acid.

3. The method for preparing an aqueous multifunctional binder capable of recycling positive electrode materials according to claim 1, characterized in that: In the step 1), the mass ratio of acrylic acid, chitosan and N-hydroxysuccinimide is 55-65:3-5:0.5-1.

5.

4. The method for preparing an aqueous multifunctional binder capable of recycling positive electrode materials according to claim 1, characterized in that: In the step 2), the power of the ultraviolet lamp is 16-18W, and the irradiation time is 0.5-1h.

5. The method for preparing an aqueous multifunctional binder capable of recycling positive electrode materials according to claim 1, characterized in that: The freeze-drying time in step 3) is 12 to 24 hours.

6. An aqueous multifunctional binder capable of recovering positive electrode materials, prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the aqueous multifunctional binder capable of realizing positive electrode material recovery as claimed in claim 6 in protecting positive electrode materials from corrosion by electrolyte during electrochemical cycles.

8. Use of the aqueous multifunctional binder capable of recycling positive electrode materials as claimed in claim 6 in recycling positive electrode materials.

9. The use according to claim 8, characterized in that: The solution used to recover the positive electrode material is an alkaline solution, and the pH value of the alkaline solution is 11-13.

10. The use according to claim 8, characterized in that: The method of realizing the recovery of positive electrode materials also includes supplementing lithium with the recovered positive electrode materials to obtain lithium-supplemented positive electrode materials.

Citation Information

Patent Citations

  • Aqueous liquid composition, aqueous coating, functional coating film, and composite material

    CN103384697A

  • Application of carboxymethyl chitosan self-crosslinking polymer in silicon negative electrode of lithium ion battery

    CN105702963A

  • Tough anti-swelling conductive hydrogel material as well as preparation method and application thereof

    CN117362683A

  • Polyacrylic acid / chitosan / carboxylated graphene oxide hydrogel as well as preparation method and application thereof

    CN117700775A

  • Positive electrode aqueous binder for lithium-ion battery, and preparation method therefor

    WO2022160845A1